Relationship between Obesity Incidence and Fast Food Consumption Habits in Children - Munir, Zainal; Putra, Bintang Utama; Ashfihani, Ghifari Hiban; Maulana, Fikri Aldi; Hidayatullah, Aldo Jaiz Maulana (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Childhood obesity remains a growing public health problem worldwide, including in Indonesia. One of the contributing factors is the increased consumption of fast food among children. This study aims to analyze the relationship between the frequency of fast food consumption and the incidence of obesity among elementary school children as an effort to provide scientific evidence for obesity prevention at an early age. This research used a quantitative method with a cross-sectional approach involving 70 children aged 7–12 years from selected through purposive sampling due to the high prevalence of fast food consumption and early findings showing an increase in obesity cases in the area. Data were collected using questionnaires on fast food consumption and measurements of body mass index (BMI) as an indicator of nutritional status. The chi-square test revealed a significant relationship between the frequency of fast food consumption and the incidence of obesity (p < 0.05). Although fast food consumption was found to contribute to obesity, other factors such as genetic predisposition, physical activity level, and social environmental influences may also play a role and should be considered in future studies. The findings highlight the importance of promoting nutritional education for children and parents, implementing school-based interventions, and regulating the availability of fast food around the school environment as preventive measures to control childhood obesity.